Site selection for the Hayabusa2 artificial cratering and subsurface material sampling on Ryugu. (15th September 2022) - Kikuchi, Shota; Watanabe, Sei-ichiro; Wada, Koji; Saiki, Takanao; Yabuta, Hikaru; Sugita, Seiji; Abe, Masanao; Arakawa, Masahiko; Cho, Yuichiro; Hayakawa, Masahiko; Hirata, Naoyuki; Hirata, Naru; et al.
Abstract: Hayabusa2 took on the challenge of collecting fresh subsurface samples from asteroid (162173) Ryugu during its second touchdown operation. For this ambitious goal, the spacecraft conducted artificial cratering by using a small carry-on impactor (SCI), leading to the exposure of subsurface materials. The key to mission success lies in the target site selection for the SCI and landing operations, which is the focus of this paper. On the one hand, the science goal of collecting subsurface materials required us to land on one of the areas with a large amount of impact ejecta excavated by SCI, where boulder abundance is not necessarily low. On the other hand, spacecraft safety demanded that we avoid landing on hazardous areas with large boulders. These two conditions often conflicted with each other. In order to resolve this dilemma, we developed a scheme to select a target site that secures the chance of retrieving a significant amount of subsurface samples without posing serious safety risks. Although the basic selection scheme was similar to that for the first touchdown, the second landing site selection involved additional analyses of artificial cratering and subsurface sampling. Consequently, the site selection campaign, including various types of spacecraft operations, contributed to the successful retrieval of Ryugu samples, which presumably contain materials excavated from subsurface layers. The present study provides the framework to access internal asteroid materials, pushing the envelope of space exploration. Highlights: Hayabusa2 aimed to collect subsurface samples from Ryugu excavated by an impactor. Hayabusa2 completed landing and sampling on a target site with a diameter of 3.5 ​m. The estimated thickness of the impact ejecta at the landing site was 1–3 ​cm. No hazardous boulders larger than 65 ​cm existed within the landing site.